Homenaje a Cage (2013)
In 1945, John Cage joined Henry Cowell, Lou Harrison and Virgil Thomson to create the Party Pieces: Sonorous and Exquisite Corpses, for flute, clarinet, bassoon, horn and piano. It is about 20 short pieces built with the famous surrealist technique of the “exquisite corpse”. Each composer wrote a music beat plus two notes, folded the paper to hide the composite beat and passed it to another composer who composed another beat plus two notes from the two notes left by the preceding composer. We did the same three - Andrés Posada, Victor Agudelo and Marco Alunno - to celebrate the centenary of the birth of Cage in the framework of the John Cage festival, the planned chance master that took place in Medellín throughout 2012. premiere took place on September 28, 2012 at the Museum of Modern Art in Medellín. The piece lasts just under three minutes and, unlike its illustrious model, was composed for violin, flute, clarinet and piano.